Application method of pavement heat conduction groove filling material
By using a combination of polyurethane elastic concrete and high thermal conductivity, a filling layer with good adhesion and compressive resistance is formed, which solves the problem that road heating materials cannot conduct one-way heat melting and poor stress performance, and achieves high heat efficiency One-way transmission and stability of road surface thermal conductivity grooves.
Patent Information
- Application Number
- CN202411404517.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing road heating materials cannot conduct heat and melt ice in one direction, and the stress performance of the heating structure is poor, making it easy to displace.
Use filler materials that combine polyurethane elastic concrete, floating beads and high thermal conductivity materials (such as graphite, carbon black, carbon fiber), and high-speed homogenization is carried out during the preparation of polyurethane elastic concrete to form a good bonding and compressive resistance. The first and second elastic filling layers ensure the fixation of the genital belt and the one-way transfer of heat.
The compressive strength and crack resistance of the road thermal conduction groove are improved, ensuring that heat is transferred to the road in one direction for snow melting and deicing, avoiding heat waste, and preventing the heat from displaced during driving.
Smart Images

Figure CN118908672B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pavement, and in particular to an application method of a pavement heat-conducting groove filling material. Background Art
[0002] In the cold winter, ice-covered roads pose a great safety hazard to road traffic. Traditional deicing methods, such as spreading salt or using chemical deicers, can temporarily alleviate the problem, but long-term use will not only pollute the environment, but may also cause damage to the road surface. In addition, the deicing effect of these methods is also limited by weather conditions and traffic flow.
[0003] Chinese patent publication number CN108442208B discloses a pavement structure with good thermal conductivity, including a roadbed at the bottom, a fly ash soil base layer laid flat on the roadbed, an asphalt concrete lower layer laid flat on the fly ash soil base layer, an asphalt concrete middle surface layer laid flat on the asphalt concrete lower layer, a heating layer laid flat on the asphalt concrete middle surface layer, and an asphalt concrete upper surface layer laid flat on the heating layer, wherein the heating layer includes a thermal insulation bonding layer, an electric heating film layer and a thermal conductive bonding layer, wherein the electric heating film layer is located between the thermal insulation bonding layer and the thermal conductive bonding layer, wherein the thermal insulation bonding layer is bonded to the asphalt concrete middle surface layer, and the thermal conductive bonding layer is bonded to the asphalt concrete upper surface layer; the pavement structure with good thermal conductivity of the invention can better remove snow and ice on the road in a timely manner without affecting road traffic. However, the stress-bearing performance and compressive resistance of the pavement structure are relatively poor, and the coating thickness of the thermal insulation bonding layer and the thermal conductive bonding layer is only 1 mm, and the pavement thermal conductive structure is easily displaced when vehicles pass by.
[0004] Chinese patent publication number CN109626873A discloses a high thermal conductivity asphalt mixture and a pavement structure prepared therefrom. The high thermal conductivity asphalt mixture provided by the invention includes epoxy asphalt, modified epoxy resin, calcium carbonate-coated hexagonal boron nitride composite particles, nano-silica, mineral fiber, aggregate, methyl hexahydrophthalic anhydride, benzyldimethylamine, and silane coupling agent. The calcium carbonate-coated hexagonal boron nitride composite particles, nano-silica and mineral fiber synergistically construct a high thermal conductivity and high insulation network chain structure, so that the thermal conductivity and system resistivity of the structure prepared by the mixture are both large. The pavement can quickly transfer heat to the first asphalt concrete layer, melt the snow on the road surface in time, prevent the road surface from freezing, and ensure the normal passage of vehicles; at the same time, the pavement will not have leakage phenomenon, ensuring the safety of pedestrians and vehicles. However, the pavement structure prepared by the high thermal conductivity asphalt mixture described above cannot have the function of unidirectionally and upwardly transferring heat to the road surface to melt snow and remove ice, resulting in waste of heat energy. Summary of the invention
[0005] Therefore, in view of the above problems, the present invention provides an application method of a pavement heat-conducting groove filling material to solve the problems that the existing pavement heating materials cannot conduct heat to melt ice in a unidirectional manner, and the heating structure has poor stress-bearing performance and is prone to displacement.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for applying a pavement heat-conducting groove filling material comprises the following steps:
[0008] S1. The following raw materials are used: polyurethane elastic concrete, high thermal conductivity material and floating beads; the polyurethane elastic concrete comprises the following raw materials in parts by weight: 5-8 parts by weight of polyurethane elastic material, 10-15 parts by weight of cement, 70-80 parts by weight of mixed aggregate and 10-25 parts by weight of dewatering agent;
[0009] S2, adding the floating beads to the polyurethane elastic concrete at a weight ratio of 1:10-1:12 at a temperature of 140°C-160°C, adding and stirring at the same time, after the floating beads are completely added, high-speed homogenization is performed to obtain a first mixture, the first mixture is filled into the bottom of the pavement heat conduction groove to obtain a first elastic filling layer, and the heat-generating belt is immediately installed into the pavement heat conduction groove, and waits for solidification;
[0010] S3. According to the weight ratio of high thermal conductivity material to polyurethane elastic concrete of 1:4-1:7, at a temperature of 140°C-160°C, add the high thermal conductivity material to the polyurethane elastic concrete, adopt a method of adding and stirring, after the high thermal conductivity material is completely added, perform high-speed homogenization to obtain a second mixture, and fill the second mixture to the outside of the top of the above-mentioned heat-generating belt to obtain a second elastic filling layer.
[0011] Furthermore, the general structural formula of the polyurethane elastic material is as follows (1):
[0012] (1)
[0013] In the formula: R1 is an ether chain oligomer having at least 2 hydroxyl groups at the terminal group, and R2 is an oligomeric isocyanate having 3-6 isocyanate groups.
[0014] Furthermore, the preparation process of the polyurethane elastic concrete is as follows:
[0015] a. Dewater the cement and mixed aggregate, seal them, and cool them to room temperature for later use;
[0016] b. Stirring and mixing the cement, mixed aggregate and water removing agent after the primary water removal treatment to be uniform, and performing secondary water removal treatment to obtain a third mixture, which is sealed and stored for standby use;
[0017] c. Fully stir the polyurethane elastic material and the third mixture obtained in step b at 140° C.-160° C., and perform high-speed homogenization to obtain the polyurethane elastic concrete.
[0018] Furthermore, the high thermal conductivity material is any one of graphite, carbon black, and carbon fiber, or a mixture of two or more of them in any proportion.
[0019] Furthermore, the cement is PO 42.5 ordinary Portland cement.
[0020] Furthermore, the mixed aggregate comprises: 5-30 parts by weight of AC-5 sand-type concrete, 5-35 parts by weight of AC-10 fine-grained concrete and 5-25 parts by weight of AC-13 fine-grained concrete; the particle size of the mixed aggregate is 0.1 mm-15 mm.
[0021] Furthermore, the dehydrating agent is 5A molecular sieve activated powder; the particle size of the dehydrating agent is 2mm-4mm.
[0022] Furthermore, the high-speed homogenization treatment is carried out in a high-speed shearing instrument at a shearing speed of 5000 r / min-5500 r / min, a time of 10 min-20 min, and a temperature of 140° C.-160° C.
[0023] Furthermore, the primary water removal treatment is drying in a forced air drying oven at a temperature of 130° C.-150° C. for a time of 4 h-6 h.
[0024] By adopting the above technical solution, the beneficial effects of the present invention are:
[0025] Polyurethane elastic material, cement, mixed aggregate and dewatering agent are used as raw materials to prepare polyurethane elastic concrete, wherein cement particles are evenly distributed in the polyurethane elastic material and tightly wrapped by the polyurethane elastic material, having good adhesion, and can better fix the heat-generating belt inside the heat-conducting groove to prevent the heat-generating belt from being displaced when vehicles pass by on the road. The heat-conducting groove includes a pair of mirror-symmetrically arranged steel sections and cover seam plates, which can withstand the pressure of pedestrians and vehicles and have good strength, crack resistance and compression resistance. At the same time, the addition of polyurethane elastic material can prevent the generation of cracks. The particle size of the mixed aggregate is 0.1-15 mm, which can be fully filled into the fine pores inside the polyurethane elastic concrete, making the internal structure of the polyurethane elastic concrete more compact, thereby having excellent force-bearing performance.
[0026] The floating beads are hollow fly ash balls, the main components of which are silicon dioxide and aluminum oxide. The thermal conductivity is only 0.08-0.1 W / m·K, and they are good thermal insulation materials. They are filled into the bottom of the heat-conducting groove of the road surface to form a first elastic filling layer, which can prevent the heat generated by the heating belt from being transferred downward, and the countless fine pores on the surface of silicon dioxide make the floating beads have excellent properties of strong adsorption, sound insulation and heat preservation. High thermal conductivity materials include graphite, carbon black, and carbon fiber. The thermal conductivity of concrete is generally in the range of 0.7~1W / m·K. The high thermal conductivity material and polyurethane elastic concrete are evenly mixed to obtain a second mixture, and the second mixture is filled into the outer side of the top of the above-mentioned heating belt to obtain a second elastic filling layer, which can increase the thermal conductivity of the second elastic filling layer to 2.13-2.45 W / m·K. The larger the thermal conductivity, the faster the heat energy diffuses, which can transfer heat upward to the road surface for snow melting and de-icing, avoiding heat waste and improving the efficiency of snow melting and de-icing.
[0027] In the process of preparing polyurethane elastic concrete, two dehydration treatments were carried out. One dehydration treatment was drying in a forced air drying oven, which could remove most of the water molecules adsorbed on the surface of cement and mixed aggregate. A dehydrating agent was then added to remove the remaining moisture to avoid affecting the viscosity of the polyurethane elastic material when it comes into contact with water, resulting in more pores, and thus affecting the strength of the polyurethane elastic concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a schematic diagram of the organic synthesis of the polyurethane elastic material in Example 1 of the present invention;
[0029] Figure 2 is a schematic diagram of the organic synthesis of the polyurethane elastic material in Example 2 of the present invention;
[0030] Figure 3 It is a schematic diagram of the organic synthesis of the polyurethane elastic material in Example 3 of the present invention. DETAILED DESCRIPTION
[0031] Example 1
[0032] A method for applying a pavement heat-conducting groove filling material comprises the following steps:
[0033] (1) Selection of raw materials
[0034] Polyurethane elastic concrete, graphite, floating beads; the polyurethane elastic concrete comprises the following raw materials in parts by weight: 5 parts by weight of polyurethane elastic material, 10 parts by weight of PO 42.5 ordinary Portland cement, 70 parts by weight of mixed aggregate, and 10 parts by weight of dewatering agent;
[0035] (2) Preparation of polyurethane elastic materials
[0036] The polyoxypropylene triol and triphenylmethane triisocyanate are added to the polyoxypropylene triol in a mass ratio of 1:1, and the mixture is stirred and mixed until the mixture is in a fluid state, and triethylene diamine is dropped thereinto, and the mixture is quickly stirred and mixed to obtain the polyurethane elastic material;
[0037] Specifically, the molecular structure of the polyurethane elastic material is shown in formula (2):
[0038] (2)
[0039] Specifically, the organic synthesis route of the polyurethane elastic material is as follows Figure 1 As shown;
[0040] (3) Preparation of polyurethane elastic concrete
[0041] (3-1) Dry the cement and mixed aggregate in a forced air drying oven at 130°C for 4 hours, remove water, seal and store, and cool to room temperature for later use;
[0042] (3-2) The dewatered cement, mixed aggregate and 5A molecular sieve activated powder with a particle size of 2 mm are stirred and mixed uniformly, and a second dewatering treatment is performed to obtain a third mixture, which is sealed and stored for later use;
[0043] (3-3) at 140° C., the polyurethane elastic material and the third mixture obtained in step (3-2) are fully stirred, and subjected to high-speed homogenization treatment in a high-speed shearing instrument at a shearing speed of 5000 r / min, a time of 10 min, and a temperature of 140° C., to obtain the polyurethane elastic concrete;
[0044] (4) Adding the floating beads to the polyurethane elastic concrete at a weight ratio of 1:10 at a temperature of 140° C., stirring while adding, and after the floating beads are completely added, high-speed homogenization is performed to obtain a first mixture, and the first mixture is filled into the bottom of the pavement heat conduction groove to obtain a first elastic filling layer, and the heat-generating belt is immediately installed into the pavement heat conduction groove and waited for solidification;
[0045] (5) adding graphite to the polyurethane elastic concrete at a weight ratio of 1:4 at a temperature of 140° C., adding and stirring until the graphite is completely added, and then performing high-speed homogenization to obtain a second mixture, and filling the second mixture to the outside of the top of the heat-generating belt to obtain a second elastic filling layer.
[0046] Example 2
[0047] A method for applying a pavement heat-conducting groove filling material comprises the following steps:
[0048] (1) Selection of raw materials
[0049] Polyurethane elastic concrete, carbon black, floating beads; the polyurethane elastic concrete comprises the following raw materials in parts by weight: 6 parts by weight of polyurethane elastic material, 12 parts by weight of PO 42.5 ordinary Portland cement, 75 parts by weight of mixed aggregate, and 20 parts by weight of dewatering agent;
[0050] (2) Preparation of polyurethane elastic materials
[0051] The polyoxypropylene glycol and tetraphenylmethane tetraisocyanate are added in a mass ratio of 1:1, and the mixture is stirred and mixed until the mixture is in a flowing state, and triethylene diamine is dropped thereinto, and the mixture is quickly stirred and mixed to obtain the polyurethane elastic material;
[0052] Specifically, the molecular structure of the polyurethane elastic material is shown in formula (3):
[0053] (3)
[0054] Specifically, the organic synthesis route of the polyurethane elastic material is as follows Figure 2 As shown;
[0055] (3) Preparation of polyurethane elastic concrete
[0056] (3-1) Dry the cement and mixed aggregate in a forced air drying oven at 150°C for 5 hours to remove water, seal and store, and cool to room temperature for later use;
[0057] (3-2) The dewatered cement, mixed aggregate and 5A molecular sieve activated powder with a particle size of 3 mm are stirred and mixed uniformly, and a second dewatering treatment is performed to obtain a third mixture, which is sealed and stored for later use;
[0058] (3-3) at 150° C., the polyurethane elastic material and the third mixture obtained in step (3-2) are fully stirred, and subjected to high-speed homogenization treatment in a high-speed shearing instrument at a shearing speed of 5200 r / min, a time of 15 min, and a temperature of 150° C., to obtain the polyurethane elastic concrete;
[0059] (4) Adding the floating beads to the polyurethane elastic concrete at a weight ratio of 1:12 at a temperature of 150° C., stirring while adding, and after the floating beads are completely added, high-speed homogenization is performed to obtain a first mixture, and the first mixture is filled into the bottom of the pavement heat conduction groove to obtain a first elastic filling layer, and the heat-generating belt is immediately installed into the pavement heat conduction groove and waited for solidification;
[0060] (5) Adding carbon black to polyurethane elastic concrete at a weight ratio of 1:5 at a temperature of 150° C., stirring while adding until the carbon black is completely added, and then performing high-speed homogenization to obtain a second mixture, and filling the second mixture to the outside of the top of the above-mentioned heat-generating belt to obtain a second elastic filling layer.
[0061] Example 3
[0062] refer to Figure 3 , a method for applying a pavement heat-conducting groove filling material, comprising the following steps:
[0063] (1) Selection of raw materials
[0064] Polyurethane elastic concrete, carbon fiber, floating beads; the polyurethane elastic concrete comprises the following raw materials in parts by weight: 8 parts by weight of polyurethane elastic material, 15 parts by weight of PO 42.5 ordinary Portland cement, 80 parts by weight of mixed aggregate, and 25 parts by weight of dewatering agent;
[0065] (2) Preparation of polyurethane elastic materials
[0066] The polytetramethylene glycol and triphenylmethane triisocyanate are added to the polytetramethylene glycol in a mass ratio of 1:1, and the mixture is stirred and mixed until the mixture is in a flowing state, and triethylene diamine is dropped thereinto, and the mixture is quickly stirred and mixed to obtain the polyurethane elastic material;
[0067] Specifically, the molecular structure of the polyurethane elastic material is shown in formula (4):
[0068] (4)
[0069] Specifically, the organic synthesis route of the polyurethane elastic material is as follows Figure 3 As shown;
[0070] (3) Preparation of polyurethane elastic concrete
[0071] (3-1) Dry the cement and mixed aggregate in a forced air drying oven at 150°C for 6 hours to remove water, seal and store, and cool to room temperature for later use;
[0072] (3-2) The dewatered cement, mixed aggregate and 5A molecular sieve activated powder with a particle size of 4 mm are stirred and mixed uniformly, and a second dewatering treatment is performed to obtain a third mixture, which is sealed and stored for later use;
[0073] (3-3) at 160° C., the polyurethane elastic material and the third mixture obtained in step (3-2) are fully stirred, and high-speed homogenization is performed in a high-speed shearing instrument at a shearing speed of 5500 r / min, a time of 20 min, and a temperature of 160° C. to obtain the polyurethane elastic concrete;
[0074] (4) Add the floating beads to the polyurethane elastic concrete at a weight ratio of 1:12 at a temperature of 160° C. After the floating beads are completely added, high-speed homogenization is performed to obtain a first mixture, and the first mixture is filled into the bottom of the pavement heat conduction groove to obtain a first elastic filling layer, and the heat-generating belt is immediately installed into the pavement heat conduction groove and waited for solidification;
[0075] (5) Adding carbon fiber to polyurethane elastic concrete at a weight ratio of 1:7 at a temperature of 160° C., stirring while adding until the carbon fiber is completely added, and then performing high-speed homogenization to obtain a second mixture, and filling the second mixture to the outside of the top of the above-mentioned heat-generating belt to obtain a second elastic filling layer.
[0076] Comparative Example 1
[0077] The difference from Example 1 is that the raw material does not use the polyurethane elastic material used in the present invention, but uses commercially available epoxy resin; the structure does not use a structure in which floating beads and polyurethane elastic concrete are mixed and filled at the bottom of the pavement heat conduction groove to form a first elastic filling layer, and a high thermal conductivity material and polyurethane elastic concrete are mixed and filled at the top of the heat-generating belt to form a second elastic filling layer; a pavement structure in which a first epoxy resin concrete layer, a heat-generating layer, and a second epoxy resin concrete layer are arranged in sequence from top to bottom is used, and the raw materials of the first epoxy resin concrete layer and the second epoxy resin concrete layer are the same. Other technical solutions are the same as Example 1.
[0078] The test results of Example 1, Example 2, Example 3 and Comparative Example 1 are shown in Table 1.
[0079] Table 1
[0080]
[0081] Thermal conductivity test method: Use DRM-II thermal conductivity tester for testing.
[0082] Test method for compressive strength: Test in accordance with "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020).
[0083] The test results in Table 1 show that: the thermal conductivity of the first elastic filling layer of the products of Example 1, Example 2 and Example 3 is relatively high, which are 2.09, 2.13 and 2.45 respectively, and have good heat transfer performance; the thermal conductivity of the second elastic filling layer is relatively low, which are 0.53, 0.57 and 0.62 respectively, and have good thermal insulation performance, which can facilitate the unidirectional and upward transfer of heat to the road surface for melting ice and snow removal; the thermal conductivity of the first epoxy resin concrete layer and the second epoxy resin concrete layer of Comparative Example 1 is also relatively high, which are 1.87 and 1.89 respectively, but the heat cannot be transferred unidirectionally upward, which will cause waste of heat energy; the compressive strength of the products of Example 1, Example 2 and Example 3 are all higher than 60.6MPa, which is better than the compressive strength data of Comparative Example 1.
[0084] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.
Claims
1. A method for applying a pavement heat-conducting groove filling material, characterized in that: The following steps are involved: S1. The following raw materials are used: polyurethane elastic concrete, high thermal conductivity material and floating beads; the polyurethane elastic concrete comprises the following raw materials in parts by weight: 5-8 parts by weight of polyurethane elastic material, 10-15 parts by weight of cement, 70-80 parts by weight of mixed aggregate and 10-25 parts by weight of dewatering agent; S2, adding the floating beads to the polyurethane elastic concrete at a weight ratio of 1:10-1:12 at a temperature of 140°C-160°C, adding and stirring at the same time, after the floating beads are completely added, high-speed homogenization is performed to obtain a first mixture, the first mixture is filled into the bottom of the pavement heat conduction groove to obtain a first elastic filling layer, and the heat-generating belt is immediately installed into the pavement heat conduction groove, and waits for solidification; S3, according to the weight ratio of high thermal conductivity material to polyurethane elastic concrete of 1:4-1:7, at a temperature of 140°C-160°C, adding the high thermal conductivity material to the polyurethane elastic concrete, using a method of adding and stirring, after the high thermal conductivity material is completely added, high-speed homogenization is performed to obtain a second mixture, and the second mixture is filled to the outside of the top of the above-mentioned heat-generating belt to obtain a second elastic filling layer; The general structural formula of the polyurethane elastic material is as follows: (1) In the formula: R1 is an ether chain oligomer having at least 2 hydroxyl groups at the terminal group, and R2 is an oligomeric isocyanate having 3-6 isocyanate groups.
2. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The preparation process of the polyurethane elastic concrete is as follows: a. Dewater the cement and mixed aggregate, seal them, and cool them to room temperature for later use; b. Stirring and mixing the cement, mixed aggregate and water removing agent after the primary water removal treatment to be uniform, and performing secondary water removal treatment to obtain a third mixture, which is sealed and stored for standby use; c. Fully stir the polyurethane elastic material and the third mixture obtained in step b at 140° C.-160° C., and perform high-speed homogenization to obtain the polyurethane elastic concrete.
3. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The high thermal conductivity material is any one of graphite, carbon black and carbon fiber, or a mixture of two or more of them in any proportion.
4. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The cement is PO 42.5 ordinary Portland cement.
5. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The mixed aggregate comprises: 5-30 parts by weight of AC-5 sand-type concrete, 5-35 parts by weight of AC-10 fine-grained concrete and 5-25 parts by weight of AC-13 fine-grained concrete; the particle size of the mixed aggregate is 0.1 mm-15 mm.
6. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The dehydrating agent is 5A molecular sieve activated powder; the particle size of the dehydrating agent is 2mm-4mm.
7. The method for applying a pavement heat-conducting groove filling material according to claim 1, characterized in that: The high-speed homogenization treatment is carried out in a high-speed shearing instrument at a shearing speed of 5000 r / min-5500 r / min, a time of 10 min-20 min, and a temperature of 140° C.-160° C.
8. The method for applying a pavement heat-conducting groove filling material according to claim 2, characterized in that: The primary water removal treatment is drying in a blast drying oven at a temperature of 130° C.-150° C. for a time of 4 h-6 h.
Citation Information
Patent Citations
A road surface structure with good thermal conductivity
CN108442208B
High-thermal-conductivity asphalt mixture and road surface structure prepared from same
CN109626873A
Pavement paving structure for melting snow and ice and using method thereof
CN111021180A